Potential Abuse of the Dominant Position of Indonesian Islamic Banks in Legal Perspective Business Competition - Muhammad Khutub (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2022)
Abstract: This objective study to examine the potential for abuse of the dominant position in Article 25 of Law no. 5/1999 in the context of business competition law against Bank Syariah Indonesia (Bank Syariah Indonesia). The Bank Syariah Indonesia merger is intended to increase the competitiveness of Islamic Commercial Banks (BUS) in providing services to customers so that they are equivalent to the services of conventional commercial banks. As is well known, the implementation of the Bank Syariah Indonesia merger has resulted in the potential for abuse of the dominant position in the Islamic banking industry, where Islamic commercial banks (BUS) have been reduced from 14 to 12. This activity also has the possibility of unfair business competition, which is clearly prohibited. according to Law no. 5/1999. The research method used is library research where the research is descriptive with a juridical-normative approach taken from secondary data through library research by analyzing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the study, it is understood that the potential for abuse of the dominant position in Bank Syariah Indonesia is not only seen from its competitors, namely other Islamic banks, but also must be seen from the perspective of customers and the community as service users also play an active role in assessing customer satisfaction based on their respective performances. banking sector. So far, based on the criteria of article 25 above, Bank Syariah Indonesia is very far from the potential for abuse of its dominant position, even though in its assessment Bank Syariah Indonesia is in a dominant position.Abstrak: Penelitian ini bertujuan untuk mengkaji potensi penyelahgunaan posisi dominan dalam pasal 25 UU No. 5/1999 dalam konteks hukum persaingan usaha terhadap Bank Syariah Indonesia (Bank Syariah Indonesia). Merger Bank Syariah Indonesia dimaksudkan untuk meningkatkan daya saing Bank Umum Syariah (BUS) dalam memberikan pelayanan kepada nasabah agar setara dengan pelayanan bank umum konvensional. Seperti yang diketahui, penyelenggaraan merger Bank Syariah Indonesia ini menyebabkan potensi terjadinya penyalahgunaan posisi dominan dalam industri perbankan syariah, di mana bank umum syariah (BUS) menjadi berkurang, dari 14 menjadi 12. Kegiatan ini juga mempunyai kemungkinan terjadinya tindak persaingan usaha tidak sehat yang secara jelas dilarang sesuai UU No. 5/1999. Metode penelitian yang digunakan merupakan library research di mana penelitian bersifat deskriptif dengan pendekatan yuridis-normatif yang diambil dari data sekunder melalui riset kepustakaan dengan menganalisis data dari bahan hukum primer, bahan hukum sekunder dan bahan hukum tersier. Berdasarkan hasil penelitian dipahami bahwa potensi penyalahgunaan posisi dominan pada Bank Syariah Indonesia tidak melulu dilihat dari pesaingnya, yaitu bank-bank syariah lain, tetapi juga harus dilihat dari perspketif nasabah dan masyarakat sebagai pengguna layanan juga turut berperan aktif dalam melakukan penilaian kepuasan konsumen berdasarkan kinerja masing-masing perbankan.Adapun Bank Syariah Indonesia sejauh ini berdasarkan kriteria pasal 25 di atas, sangat jauh dari potensi penyalahgunaan posisi dominannya, meskipun dalam peniliannya Bank Syariah Indonesia berada pada posisi dominan.